A influência do pacto de São José da Costa Rica no que tange a prisão civil do depositário infiel no instituto da alienação fiduciária no direito brasileiro - Bernardi, Cariane (My University, 2020)
With the development and evolution of society, the need to expand human rights was observed in the legal environment. For this advance, there is the development of international treaties aimed at these improvements at the international level, but which have a strong role in the domestic law of countries. In Brazil, specifically, one of these treaties had an influence, even, on the collection means admitted in the fiduciary sale, an institute that is used in a wide range in the economic market of movable and real estate. Thus, the present work aims to analyze how the interference of this international treaty, namely the San José Pact of Costa Rica, actually occurred, in one of the main means used to provoke the party against the fulfillment of its obligation assumed in the fiduciary business, on the tangent of the infidel depositary's civil prison. It was found that the change in the understanding of the Supreme Federal Court on this issue, due to the prevalence of human rights before the Federal Constitution, brought about the prohibition of civil imprisonment of the unfaithful depositary, and it is no longer possible to use this means of collection as form of coercion of the fiduciary debtor to fulfill the obligation in the fiduciary alienation contracts, and it is necessary to seek other means of collection, such as, for example, the enforcement process (sic).
Com o desenvolvimento e evolução da sociedade, foi observada no meio jurídico a necessidade de ampliação dos direitos humanos. Para esse avanço há o desenvolvimento dos tratados internacionais que visam essas melhorias em âmbito internacional, mas que possuem forte atuação no direito interno dos países. No Brasil, especificamente, um desses tratados apresentou influência, inclusive, nos meios de cobrança admitidos na alienação fiduciária, instituto que é utilizado em larga escada no mercado econômico de bens móveis e imóveis. Dessa forma, o presente trabalho visa analisar como de fato ocorreu a interferência desse tratado internacional, qual seja, o Pacto de São José da Costa Rica, num dos principais meios utilizados para provocação da parte contrária ao cumprimento de sua obrigação assumida no negócio fiduciário, na tangente da prisão civil do depositário infiel. Verificou-se que a mudança do entendimento do Supremo Tribunal Federal a respeito desse tema, em função da prevalência dos direitos humanos perante a Constituição Federal, trouxe a proibição da prisão civil do depositário infiel, não sendo mais possível a utilização desde meio de cobrança como forma de coação do devedor fiduciante ao cumprimento da obrigação nos contratos de alienação fiduciária, sendo necessário buscar outros meios de cobrança, como, por exemplo, o processo de execução (sic).
Keywords: Direitos humanos; Alienação fiduciária; Prisão